2009
DOI: 10.1111/j.1742-4658.2009.07384.x
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of nuclear DNA‐encoded subunits into mitochondrial complex IV, and their preferential integration into supercomplex forms in patient mitochondria

Abstract: Complex IV is the terminal enzyme of the mitochondrial respiratory chain. In humans, biogenesis of complex IV involves the coordinated assembly of 13 subunits encoded by both mitochondrial and nuclear genomes. The early stages of complex IV assembly involving mitochondrial DNA‐encoded subunits CO1 and CO2 have been well studied. However, the latter stages, during which many of the nuclear DNA‐encoded subunits are incorporated, are less well understood. Using in vitro import and assembly assays, we found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 48 publications
(115 reference statements)
5
71
0
Order By: Relevance
“…Mitochondrial cardiomyopathy has been associated with numerous mutations in both mitochondrial and nuclear DNA-encoded genes (14,(35)(36)(37)(38). Our data indicate that genetic lesions affecting Mediator complex subunits should also be considered as a possible cause of primary cardiomyopathies in humans, particularly in pediatric cases given the importance of MED30 to early cardiac function during the period of weaning in mice.…”
Section: Dissection Of Moribund Med30mentioning
confidence: 99%
“…Mitochondrial cardiomyopathy has been associated with numerous mutations in both mitochondrial and nuclear DNA-encoded genes (14,(35)(36)(37)(38). Our data indicate that genetic lesions affecting Mediator complex subunits should also be considered as a possible cause of primary cardiomyopathies in humans, particularly in pediatric cases given the importance of MED30 to early cardiac function during the period of weaning in mice.…”
Section: Dissection Of Moribund Med30mentioning
confidence: 99%
“…COX7A has been considered as a late-assembling subunit similar to COX6A ref. 29, and in vitro translated COX7A was first incorporated into complex IV and supercomplex III þ IV based on in vitro import and assembly assays 30 . Thus, it is likely that COX7A has a role in the late steps of holo-complex IV formation, as well as in the assembly of III and IV, and is located in the periphery of complex IV.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse-chase experiments that analyzed the time-course incorporation of the thirteen mitochondrial-encoded proteins into RC complexes and supercomplexes suggested that supercomplexes originated by the direct association of single fully-assembled complexes (Acin-Perez et al, 2008). However, the observation that, in the absence of monomeric complex IV, newly-imported nuclear subunits from this complex were preferentially integrated into supercomplexes, suggested that the respirasomes formation could also be achieved through the association of partiallyassembled complexes and free subunits (Lazarou et al, 2009). In a recent study, our group addressed the biosynthetic pathway of mitochondrial RC supercomplexes by partially depleting control cell lines of OXPHOS complexes with doxycycline, a reversible inhibitor of mitochondrial translation.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 99%